Mononuclear chelates derived from substituted Schiff base ligands: Synthesis and characterization of a new 3-methoxysalicyliden-p-aminoacetophenoneoxime and its complexes with Co(II), Ni(II), Cu(II), and Zn(II) - Canpolat, E; Kaya, M; Yazici, A (Taylor & Francis Inc, 2005)
A new Schiff base ligand, 3-methoxysalicyliden-p-aminoacetophenoneoxime (LH), was synthesized starting from p-aminoacetophenoneoxime and 3-methoxysalicylaldehyde. Complexes of this ligand with CO+2, Ni+2, CU+2, and Zn+2 salts were prepared. With this ligand, complexes were synthesized using CO+2, Ni+2,CU+2, and Zn+2 salts with a metal: ligand ratio of 1 : 2. Structures of the ligand and its complexes were proposed based on elemental analyses, IR, H-1- and C-13-NMR, electronic spectra, magnetic susceptibility measurements, molar conductivity, and thermogravimetric analyses (TGA).
Keywords: transition metal complexes of Schiff bases; Schiff bases